2021
DOI: 10.3390/ma14247763
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Density on the Value of Young’s Modulus for Dry Ice

Abstract: The efficiency of material consumption is an important consideration for production processes; this is particularly true for processes that use waste materials. Dry ice extrusion serves as a good example. An examination of the literature on this subject leads to an observation that the commercially available machines for dry ice compression are characterized by a high value of working force. Consequently, the effectiveness of the source consumption, electric energy and carbon dioxide, is very low. The subject … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 35 publications
0
17
0
Order By: Relevance
“…The equation obtained, in conjunction with the published results of research on the change in the value of Young's modulus as a function of density [33] z, can be used in numerical studies concerning the description of compaction processes using, for example:…”
Section: Conclusion and Results Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The equation obtained, in conjunction with the published results of research on the change in the value of Young's modulus as a function of density [33] z, can be used in numerical studies concerning the description of compaction processes using, for example:…”
Section: Conclusion and Results Discussionmentioning
confidence: 99%
“…The value of the Poisson ratio ν for a different degree of compression of the isotropic material was determined using the methodology described in [33]. It assumes that when the material is compacted in a closed chamber, the transverse strains ε x and ε y are equal to 0, and the strains σ x and σ y acting on the chamber's side walls are equal to each other.…”
Section: Methodsmentioning
confidence: 99%
“…It has been demonstrated that the value of this force depends on the die parameters and the coefficient of friction between the extruded material and the side walls of the die [18]. The value of Fe decreases as the process of extrusion proceeds and the density of the material ρ no longer increases as a result [20]. The graph in Figure 2 represents the change of F e as a function of ram displacement s, subdivided into three main phases of the change of force applied to extrude dry ice pellets.…”
Section: Introductionmentioning
confidence: 99%
“…It has been demonstrated that the value of this force depends on the die parameters and the coefficient of friction between the extruded material and the side walls of the die [18]. The value of Fe decreases as the process of extrusion proceeds and the density of the material ρ no longer increases as a result [20]. Compression of the material reduces the distances between the particles of the material observed as an increase in density ρ.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation